2017
DOI: 10.1103/physrevlett.119.130401
|View full text |Cite
|
Sign up to set email alerts
|

Nonexponential Quantum Decay under Environmental Decoherence

Abstract: A system prepared in an unstable quantum state generally decays following an exponential law, as environmental decoherence is expected to prevent the decay products from recombining to reconstruct the initial state. Here we show the existence of deviations from exponential decay in open quantum systems under very general conditions. Our results are illustrated with the exact dynamics under quantum Brownian motion and suggest an explanation of recent experimental observations.The exponential decay law of unstab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 50 publications
0
50
0
Order By: Relevance
“…Thus one can assume that the total system collapses to its initial state after each measurement. Moreover, the decay pattern of an openquantum system is often nonexponential [54]. One can always use the effective decay rate to describe the system evolution in a moderate time scale under the weakcoupling approximation.…”
Section: A Weak-coupling Regimementioning
confidence: 99%
“…Thus one can assume that the total system collapses to its initial state after each measurement. Moreover, the decay pattern of an openquantum system is often nonexponential [54]. One can always use the effective decay rate to describe the system evolution in a moderate time scale under the weakcoupling approximation.…”
Section: A Weak-coupling Regimementioning
confidence: 99%
“…with C, γ > 0 and q < 1. In physical terms, the origin of this slower decay can be traced back to the possibility that the time-evolving state reconstructs the initial state [38,49,50]. The specific form of the long-time decay depends on the behavior of the LDOS near any edges.…”
Section: Long-time Power-law Decaymentioning
confidence: 99%
“…While QSL provide fundamental constraints to the pace at which quantum systems can change, a plethora of applications have been found that well extend beyond the realm of quantum dynamics. Indeed, QSL provide limits to the computational capability of physical devices [5], the performance of quantum thermal machines in finite-time thermodynamics [6,7], parameter estimation in quantum metrology [8,9], quantum control [10][11][12][13][14], the decay of unstable quantum systems [15][16][17][18] and information scrambling [19], among other examples [3,4,20].Specifically, QSL are derived as upper bounds to the rate of change of the fidelity F(τ) = | ψ 0 |ψ τ | 2 ∈ [0, 1] between an initial quantum state |ψ 0 and the corresponding time-evolving state |ψ τ =Û(τ, 0)|ψ 0 , whereÛ(τ, 0) is the time-evolution operator. More generally quantum states need not be pure, and given two density matrices ρ 0 and ρ τ =Û(τ, 0)ρ 0Û (τ, 0) † the fidelity readsThe fidelity is useful to define a metric between quantum states in Hilbert space, known as the Bures angle, [24,25] This gives a geometric interpretation of speed limit as the minimum time required to sweep out the angle L (ρ 0 , ρ τ ) under a given dynamics [26].…”
mentioning
confidence: 99%